Pathways of change: Schools as building blocks towards nurturing biodiversity and resilient agricultural and food systems - Kipkorir, Langat; Apondi, Victoria; Fuchs, Lisa Elena (2025)
When we think of schools, we often imagine classrooms, textbooks, and examinations. Yet, schools hold untapped potential to serve as mini-Living Labs for sustainable food system transformation, bridging the gap between ecological farming, ecosystem restoration, and community resilience.